2011
DOI: 10.5121/ijwmn.2011.3308
|View full text |Cite
|
Sign up to set email alerts
|

Routing Techniques In Cognitive Radio Networks: A Survey

Abstract: Cognitive Radio Networks (CRNs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…reactive, proactive, multi‐cast and hierarchical protocols that are available for such type of networks. Thus, the focus is now on evaluating the novel routing protocols for CRNs, since routing is regarded to be a difficult task for such type of networks, especially in multi‐hop CRNs because of varying channel availability as well as data rates [13]. A brief overview pertaining to the research with regards to routing for CRNs has identified two distinct key categories: approaches that build on full spectrum knowledge, and approaches that only regard the local spectrum knowledge gained via distributed procedures as well as protocols, as given in [14].…”
Section: Related Workmentioning
confidence: 99%
“…reactive, proactive, multi‐cast and hierarchical protocols that are available for such type of networks. Thus, the focus is now on evaluating the novel routing protocols for CRNs, since routing is regarded to be a difficult task for such type of networks, especially in multi‐hop CRNs because of varying channel availability as well as data rates [13]. A brief overview pertaining to the research with regards to routing for CRNs has identified two distinct key categories: approaches that build on full spectrum knowledge, and approaches that only regard the local spectrum knowledge gained via distributed procedures as well as protocols, as given in [14].…”
Section: Related Workmentioning
confidence: 99%
“…The Classification of Mobile Cognitive radio Ad hoc networks [4] is of two types, which is described in the following Figure 1.…”
Section: Classification Of Cognitive Radio Networkmentioning
confidence: 99%
“…In CR ad hoc networks, a node may not be able to transmit immediately if it detects the presence of a Primary user on the spectrum. [6] In MCRANs, unidirectional links are more possible [4]. Such links will be available for a fraction of time instead of minutes or hours.…”
Section: Cognitive Radio and Ad Hoc Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive Radio Sensor Devices (CRSDs), which are also referred to as secondary users, share the licensed band with primary users (PUs) who have higher priorities in occupying the bands in a non-interfered manner. This indicates that the topology of CRSN is changing un-predictably due to PUs' activities and causes considerable difficulty in guaranteeing stable and efficient communications (Cesana et al, 2011;Akan et al, 2009;Ali et al, 2011).…”
Section: Introductionmentioning
confidence: 99%